In vivo Models of HIV Disease and Control - Friedman, Herman; Specter, Steven; Bendinelli, Mauro (Infectious Agents and Pathogenesis, 2006)
An AIDS vaccine is still elusive and HIV treatment continues to develop multidrug resistance at alarming rates. Because of the similarities between HIV and immune deficiency infections in a variety of animals, it is only natural that scientists use these animals as models to study pathogenesis, treatment, vaccine development and many other aspects of HIV. Part of the series Infectious Agents and Pathogenesis, this volume reviews the immune deficiency virus in a variety of hosts. Pathogenesis, vaccine and drug development, epidemiology, and the natural history of the monkey, mouse, cat, cow, horse, and other animal viruses are detailed and compared to HIV. Also included are chapters on the history and future of animal models, as well as a chapter on ethical and safety considerations in using animal models for AIDS studies.